Damage morphology and mechanism in ablation cutting of thin glass sheets with picosecond pulsed lasers. (June 2016) - Sun, Mingying; Eppelt, Urs; Hartmann, Claudia; Schulz, Wolfgang; Zhu, Jianqiang; Lin, Zunqi
Abstract: We experimentally investigated the morphology and mechanism of laser-induced damage in the ablation cutting of thin glass sheets with picosecond pulsed lasers and we compared the experimental results to our models. After several passes of laser ablation, we observed two different kinds of damage morphologies on the cross-section of the cut channel. They are distinguished to be the damage region caused by high-density free-electrons and the heat-affected zone due to the heat accumulation, respectively. Furthermore, micro-cracks can be observed on the top surface of the workpiece near the cut edge. The nano-cracks could be generated by high energy free-electrons but opened and developed to be visible micro-cracks by thermal stress generated in the heat-affected zone. The crack length was proportional to the volume of heat-affected zone. Heat-affected-zone and visible-cracks free conditions of glass cutting were achieved by controlling the repetition rate and spatial overlap of laser pulses. Highlights: Damages on the cross-section are caused by free-electrons and heat accumulation. The surface crack length was proportional to the volume of heat-affected zone. Microcracks are initialized by high energy electrons but opened by thermal stress. Heat-affected-zone and visible-cracks free conditions were achieved.